Abuse against people with physical disabilities in public facilities in the UAE society - Sayyari, Nahid; Alomosh, Ahmad (Al-Adab Journal, 2023)
The study aimed to identify the Abuse against people with physical disabilities in public facilities in the UAE. To achieve the study objectives, a social survey methodology was utilized using a questionnaire as the primary data collection tool. The study was conducted on a purposive non-probability sample of 90 individuals with disabilities from the Emirati community. The study yielded several key findings, including the following: The highest age group represented was 18-25 years, predominantly male, and most of the sample consisted of Emirati individuals with a secondary education level. Regarding the forms of abuse, there was a high prevalence of harassment and bullying against people with physical disabilities by others. The study also found a statistically significant relationship between place of residence, educational level, employment status, housing situation, and the occurrence of Abuse against people with physical disabilities in public facilities. As for the resulting effects on people with physical disabilities who experienced mistreatment, the highest impact was social isolation, while the highest impact on the families of those individuals was a feeling of helplessness due to their inability to protect their child. The study provided several recommendations, including the establishment of dedicated helpline numbers for reporting incidents of Abuse against people with physical disabilities